2015
DOI: 10.1155/2015/356893
|View full text |Cite
|
Sign up to set email alerts
|

The Long Noncoding RNA MEG3 Is Downregulated and Inversely Associated with VEGF Levels in Osteoarthritis

Abstract: Osteoarthritis (OA) is becoming a major public health problem in China, especially considering the increase in average life expectancy of the population. Thus, enhanced understanding of the molecular changes associated with OA is urgently needed to develop more effective strategies for the diagnosis and treatment of this debilitating disease. LncRNAs play an important role in the processes of bone and cartilage development. Maternally expressed gene 3 (MEG3) is a maternally expressed lncRNA and may function as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 20 publications
3
95
0
Order By: Relevance
“…Long noncoding RNAs (LncRNAs) are longer than 200 nucleotides (nts) in length with no or limited protein‐coding capacity and were found to play important roles in diverse human diseases and biological processes . Mounting evidence has suggested that many lncRNAs are beregulated in diverse diseases such as tumours, diabetes, coronary heart disease, osteoarthritis and also IDD . For example, Lan and colleagues profiled lncRNA expression in degenerate disc tissues and normal adults' lumbar discs by microarray and found a total of 3081 differentially expressed lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (LncRNAs) are longer than 200 nucleotides (nts) in length with no or limited protein‐coding capacity and were found to play important roles in diverse human diseases and biological processes . Mounting evidence has suggested that many lncRNAs are beregulated in diverse diseases such as tumours, diabetes, coronary heart disease, osteoarthritis and also IDD . For example, Lan and colleagues profiled lncRNA expression in degenerate disc tissues and normal adults' lumbar discs by microarray and found a total of 3081 differentially expressed lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of lncRNAs, including ubiquitin-fold modifier conjugating enzyme 1 (5), HOX transcript antisense RNA (8), maternally expressed 3 (non-protein coding) (19), growth arrest specific 5 (non-protein coding) (7) and imprinted maternally expressed transcript (non-protein coding) (20), were reported to be significantly associated with the progression of OA. However, the functional roles of most lncRNAs in OA remain largely elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Besides miRNAs, lncRNAs also participate in the regulation of angiogenesis. MEG3 is thought to inhibit this process by reducing VEGF levels,[14] and GAS5 knockdown increases retinal neovascularization and capillary leakage. [15] In contrast, the lncRNA MALAT1 can enhance VEGF expression and promote pathological angiogenesis.…”
Section: Discussionmentioning
confidence: 99%